Characterization of Axon Damage, Neurological Deficits, and Histopathology in Two Experimental Models of Intracerebral Hemorrhage - Liu, Yao; Lu, Gang; Su, Xian Wei; Ding, Tao; Wang, Wen Li; Li, Yong Mei; Poon, Wai Sang; Ao, Li Juan (Frontiers in Neuroscience, 2018)
Spontaneous intracerebral haemorrhage (ICH) is one of the most lethal forms of stroke. From the limited previous studies and our preliminary data, white matter is considered a key predictor of the outcome and potential target of recovery. The traditional ICH model induced by injection of autologous blood or bacterial collagenase into striatum (ST) demonstrated a spontaneous functional recovery within one or two months. We hypothesis that an internal capsule (IC) lesion might lead to long-term axonal damage and long lasting functional deficits. Thus in this study, a modified internal capsule ICH model was conducted in rats, and the axonal damage, neurological deficits, histopathology as well as electrophysiology were characterized. The finding demonstrated that compared to ST group, the modified IC lesioned model exhibited a relatively smaller lesion volume with consistent axonal loss/degeneration and long-lasting neurological dysfunction at 2 months after ICH. Functionally, the impairment of the mNSS, ratio of contralateral forelimb usage, four limb stand index, contralateral duty cycle and ipsilateral SSEPs amplitude remained significant at 56 days. Structurally, the significant loss of PKCγ in ipsilateral cortical spinal tracts of IC group and the consistent axonal degeneration with several axonal retraction bulbs and enlarged tubular space was observed at 56 days after ICH. This study suggested that a modified IC lesioned model was proved to have long lasting neurological deficits. A comprehensive understanding of the dynamic progression after experimental ICH should aid further successful clinic translation in animal ICH studies, and provide new insights into the role of whiter matter injury in the mechanism and therapeutic targets of ICH.